1999
DOI: 10.3346/jkms.1999.14.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Th1 and Th2 type cytokines responding to HBsAg and HBxAg in chronic hepatitis B patients

Abstract: The cytokine pattern on viral antigen recognition is believed to exert a profound influence on the resolution of viral infections and viral clearance. This study was initiated to investigate whether a cytokine imbalance oriented toward Th2 type response plays a role in chronic hepatitis B. Cytokine profiles of peripheral blood mononuclear cells associated with chronic hepatitis B were analysed by RT-PCR. Upon HBsAg stimulation, expression of IFN-gamma, IL-2, IL-4, and IL-10 was detected in 41%, 8%, 41%, and 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…However, our study showed that the level of IFN-␥ was positively correlated with serologic markers of hepatic injury and fibrogenesis. Prior clinical reports also indicated that IFN-␥ was positively associated with elevated levels of ALT in chronic hepatitis B patients (Lee et al, 1999;Hyodo et al, 2003). The role of the elevated level of IFN-␥ in the development of hepatic injury and fibrogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study showed that the level of IFN-␥ was positively correlated with serologic markers of hepatic injury and fibrogenesis. Prior clinical reports also indicated that IFN-␥ was positively associated with elevated levels of ALT in chronic hepatitis B patients (Lee et al, 1999;Hyodo et al, 2003). The role of the elevated level of IFN-␥ in the development of hepatic injury and fibrogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Certain cytokines can contribute to this process by efficiently inhibiting viral replication when the subtype Th1 cytokine secretion pattern is predominant or by facilitating the propagation of the pathogens in the patient if the subtype Th2 cytokine secretion pattern is predominant (27).…”
mentioning
confidence: 99%
“…T-cell responses are very weak in CHB patients (8). There are two subclasses of T helper cells based on the pattern of cytokines they secrete (9), Th1 and Th2 cells, that have been found to regulate human immune systems through differentially producing cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…In those studies, the cytokine profiles of peripheral blood mononuclear cells associated with CHB were analyzed by RT-PCR, indicating that the production of IFN-γ by hepatitis B surface antigen (HBsAg)-reactive cells is associated with hepatocyte damage (8). However, the impact of ADV treatment on Th1/Th2 cytokines in CHB patients remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation